THE IMPACT OF MULTIMEDIA TOOLS ON ENGLISH VOCABULARY ACQUISITION IN PRIMARY SCHOOL STUDENTS IN UZBEKISTAN (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This research examines how multimedia tools enhance English vocabulary acquisition among primary school pupils in Uzbekistan. We investigated the integration of audio-visual materials, educational software, and interactive platforms within language instruction frameworks. Our methodology combined classroom observations, student assessments, and teacher interviews. Results indicate that students exposed to multimedia-enriched instruction demonstrated markedly higher motivation and superior retention of new vocabulary when compared with traditional pedagogical approaches. The evidence suggests that judicious implementation of technology within language classrooms can substantially improve learning outcomes.